Design and test of tilling depth measurement device based on angle sensor. (October 2019) - Li, C; He, Y; Feng, Q; Jiang, K; Wang, X; Zhang, C
Abstract: Inter-tillage is one of the most important methods to increase crop yield, reasonable tillage depth can improve crop yield and economic benefits. In the research, an angle sensor-based tillage depth measurement device was designed and its function was tested. The tillage depth measurement device was mainly composed of a supporting palm, an angle sensor, a spring, shaft components, a connection block, a regulating damper and so on, through reasonably designing the geometric structure of the supporting palm in the tillage depth measurement device and combining with the angle sensor, the information of tillage depth was converted into electrical signal, and the linear relationship between tillage depth and electrical signal was obtained. In laboratory test, the calibration and accuracy verification experiments of the tillage depth measurement device were carried out. The correlation coefficient ( r ) of reference values and measured values using the tillage depth measurement device was 0.9996 with the standard error ( SE ) of 0.08 cm. In field test, the accuracy of the tillage depth measurement device was also verified with the maximum absolute error of 0.8cm. The research results showed that the measurement device based on angle sensor had high measurement accuracy, providing a simple and direct tillage depth measurement method.